Antibacterial and remineralizing orthodontic adhesive containing quaternary ammonium resin monomer and amorphous calcium phosphate nanoparticles. (May 2018) - Liu, Yan; Zhang, Ling; Niu, Li-na; Yu, Tao; Xu, Hockin H.K.; Weir, Michael D.; Oates, Thomas W.; Tay, Franklin R.; Chen, Ji-hua
Graphical abstract: Abstract: Objectives: To evaluate the bonding performance, antibacterial activity, and remineralization effect on enamel of the orthodontic adhesive containing MAE-DB and NACP. Methods: Eighty non-carious human premolars were divided into 3 groups: Transbond XT (TB), PEHB + 5% MAE-DB (PD), and PEHB + 40% NACP + 5% MAE-DB (PND). Premolars were bonded with orthodontic brackets, the first subgroup (n = 10) and the second subgroup (n = 10) were subjected to shear bond strength testing after immersed in water for 1 day and in demineralization solution for 28 days respectively and then tested surface roughness, while the third subgroup (n = 6) was used for microhardness evaluation after aged in demineralization solution for 28 days. For each adhesive, fifty disk samples were prepared for antibacterial study. Specimens measuring 12 mm × 2 mm × 2 mm were fabricated for ion release test. Results: Bond strengths were in the order TB = PND > PND = PD for "1-day in water", and in the order TB = PND > PD for "28-days in pH 4 solution". No significant difference in the ARI scores for the three adhesive. Numerous bacteria adhered to TB surface, while PD and PND had minimal bacterial growth and activity. PND showed high levels of Ca and P ions release and enamel hardness. The surface roughness of enamel in PND was much lower than TB and PD and showed no significant difference with the sound, control enamel. Conclusion: PND adhesive with 5% MAE-DB and 40% NACP exhibits antibacterial and remineralizing capabilities, and did not adversely affect bond strength compared to commercial adhesive. Clinical significance: Novel adhesive containing quaternary ammonium monomer and nano-amorphous calcium phosphate represents a promising candidate in combating enamel white spot lesions and even dental caries.